2014
DOI: 10.1165/rcmb.2013-0437oc
|View full text |Cite
|
Sign up to set email alerts
|

Reserve Autophagic Capacity in Alveolar Epithelia Provides a Replicative Niche for Influenza A Virus

Abstract: Autophagy contributes to cellular homeostasis through metabolite recycling and degradation of cytotoxic protein aggregates and damaged organelles. Although recent studies have established that the requirement for basal autophagy is largely tissue specific, the importance of autophagy for alveolar epithelial cell homeostasis remains an important knowledge gap. In the present study we generated two mouse models, with > 90% or > 50% recombination at the Atg5 locus in the distal respiratory epithelium, to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Following inflation fixation, lung slices were incubated with 2% lanthanum nitrate in fixative at room temperature overnight, followed by routine preparation for TEM4546. Electron micrographs were collected using a Hitachi H-7650 TEM (Hitachi High Technologies America, Inc., Dallas, TX) equipped with an AMT transmission electron microscope charge-coupled device camera (Advanced Microscopy Techniques, Woburn, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Following inflation fixation, lung slices were incubated with 2% lanthanum nitrate in fixative at room temperature overnight, followed by routine preparation for TEM4546. Electron micrographs were collected using a Hitachi H-7650 TEM (Hitachi High Technologies America, Inc., Dallas, TX) equipped with an AMT transmission electron microscope charge-coupled device camera (Advanced Microscopy Techniques, Woburn, MA).…”
Section: Methodsmentioning
confidence: 99%
“…The same study showed that PINK1−/− (but not Parkin−/−) mice are protected against cigarette smoke-induced mitochondrial dysfunction 44. The deleterious role of mitophagy in COPD is challenged by recent findings in which autophagy-defective Atg5−/− aged mice displayed defective mitochondria in bronchial epithelial cells that were associated with altered lung mechanics 49. Additional evidence suggests that defective mitophagy might be detrimental as in macrophages from smokers mitophagy is impaired due to a failure in the autophagic flux (figure 3).…”
Section: Defective Mitochondrial Function In Copdmentioning
confidence: 99%
“…Interestingly, the production of specific influenza virus proteins (hemagglutinin and M2) stimulates autophagy [211], and the virus requires the autophagy pathway for optimal replication [212,213]. However, M2 concurrently limits autophagosome fusion with lysosomes [214,215].…”
Section: Pathogens Differentially Interfere With the Inflammasomes Anmentioning
confidence: 99%